Evaluation of in situ hot-rolling forming effect on plastic zone of wire + arc additively manufactured 5087 alloys using digital image correlation technique. (December 2022) - Liao, Zhen; Yang, Bing; James, M. Neil; Li, Jian; Xiao, Shoune; Wu, Shengchuan
Highlights: The HRAM-processed alloys was characterized by a finer grain size and higher tensile strength. In situ hot-rolling treatment could improve the fatigue crack propagation resistance of WAAM-processed alloys. The size of crack tip plastic zone was closely related to the grain refinement caused by hot-rolling treatment. Abstract: The fatigue crack growth (FCG) rates and crack-tip plastic zone size data for wire + arc additive manufacturing (WAAM)-processed 5087 alloys before and after in situ hot-rolling treatment were investigated and compared. After hot-rolling, the WAAM-processed alloys possessed higher strength. During the FCG tests, the crack-tip field was monitored using a digital image correlation (DIC) technique. The improved FCG resistance and smaller plastic zone area of the WAAM-processed alloys after hot-rolling were responsible for the grain refinement. Therefore, in situ hot-rolling treatment is a promising technique for optimising the properties of WAAM-processed alloys.